Preparation of graphene oxide–stabilized Pickering emulsion adjuvant for Pgp3 recombinant vaccine and enhanced immunoprotection against Chlamydia Trachomatis infection - Zhao, Lanhua; Shu, Mingyi; Chen, Hongliang; Shi, Keliang; Li, Zhongyu (Frontiers in Immunology, 2023)
Background Traditional emulsion adjuvants are limited in clinical application because of their surfactant dependence. Graphene oxide (GO) has unique amphiphilic properties and therefore has potential to be used as a surfactant substitute to stabilize Pickering emulsions. Methods In this study, GO–stabilized Pickering emulsion (GPE) was prepared and used as an adjuvant to facilitate an enhanced immune response to the Chlamydia trachomatis (Ct) Pgp3 recombinant vaccine. Firstly, GPE was prepared by optimizing the sonication conditions, pH, salinity, GO concentration, and water/oil ratio. GPE with small-size droplets was characterized and chosen as the candidate. Subsequently, controlled-release antigen delivery by GPE was explored. Cellular uptake behaviors, M1 polarization, and cytokine stimulation by GPE + Pgp3 was considered in terms of the production of macrophages. Finally, GPE’s adjuvant effect was evaluated by vaccination with Pgp3 recombinant in BALB/c mouse models. Results GPE with the smallest droplet sizes was prepared by sonication under 163 W for 2 min at 1 mg/mL GO in natural salinity with a pH of 2 when the water/oil ratio was 10:1 (w/w). The optimized average GPE droplet size was 1.8 μm and the zeta potential was –25.0 ± 1.3 mv. GPE delivered antigens by adsorption onto the droplet surface, demonstrating the controlled release of antigens both in vitro and in vivo. In addition, GPE promoted antigen uptake, which stimulated proinflammatory tumor necrosis factor alpha (TNF-α), enhancing the M1 polarization of macrophages in vitro. Macrophage recruitment was also significantly promoted by GPE at the injection site. In the GPE + Pgp3 treatment group, higher levels of immunoglobin (IgG), immunoglobin G1 (IgG1), immunoglobin G2a (IgG2a) sera, and immunoglobin A (IgA) were detected in vaginal fluid, and higher levels of IFN-γ and IL-2 secretion were stimulated, than in the Pgp3 group, showing a significant type 1 T helper (Th1)-type cellular immune response. Chlamydia muridarum challenging showed that GPE enhanced Pgp3’s immunoprotection through its advanced clearance of bacterial burden and alleviation of chronic pathological damage in the genital tract. Conclusion This study enabled the rational design of small-size GPE, shedding light on antigen adsorption and control release, macrophage uptake, polarization and recruitment, which enhanced augmented humoral and cellular immunity and ameliorated chlamydial-induced tissue damage in the genital tract.